Effect of MnO doping in tetravalent metal pyrophosphate (MP2O7; M=Ce, Sn, Zr) electrolytes - Singh B.; Kim J.-H.; Parkash O.; Song S.-J. (My University, 2025)
The poor sintering-ability of tetravalent metal pyrophosphates MP2O7 (M=Sn, Zr, Ce) has restricted their application as electrolyte in proton-conducting ceramic-electrolyte fuel cells (PCFCs). In this work, the effect of doping of MnO on the sinterability and ionic conductivity of MP2O7 is analyzed. MnO-doped MP2O7 is synthesized via a solid state reaction method. The phase composition and microstructure of MnO-doped MP2O7 are studied with X-ray diffraction (XRD) and scanning electron microscopy (SEM) and the ionic conductivity of the sintered sample is measured by electrochemical impedance spectroscopy (EIS). It is observed that, compared to the undoped sintered samples, the porosity of the MnO-doped sintered samples is greatly decreased and the ionic conductivity is significantly improved. © 2015 Elsevier Ltd and Techna Group S.r.l.